Perlindungan Hukum Bagi Pekerja Terkait Penahanan Ijazah oleh Perusahaan dalam Hubungan Industrial - Rachman, Moch. Nur; Simangunsong, Frans (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the form of legal protection for workers concerning the practice of diploma retention by companies within industrial relations. Diploma retention has increasingly appeared in recruitment processes and employment relations, despite the absence of explicit legal grounds in Indonesian labor regulations. This practice potentially violates workers’ fundamental rights, disrupts psychological well-being, restricts labor mobility, and weakens workers’ bargaining positions in industrial relations. Using a normative juridical research method, this study examines the relevant provisions of Labor Law, implementing regulations, principles of worker protection, and industrial relations theories to assess the legality and implications of diploma retention. The findings indicate that the retention of workers’ diplomas by companies contradicts the principles of freedom to work, non-discrimination, and the protection of personal documents. Legal protection for workers can be pursued through administrative, civil, and criminal mechanisms, as well as dispute resolution procedures under Law Number 2 of 2004 on Industrial Relations Dispute Settlement. This study concludes that diploma retention not only causes material and immaterial losses to workers but also negatively impacts the harmony of industrial relations. Therefore, consistent law enforcement and clearer regulations are necessary to prevent diploma retention practices and ensure the protection of workers’ rights.This study aims to analyze the form of legal protection for workers concerning the practice of diploma retention by companies within industrial relations. Diploma retention has increasingly appeared in recruitment processes and employment relations, despite the absence of explicit legal grounds in Indonesian labor regulations. This practice potentially violates workers’ fundamental rights, disrupts psychological well-being, restricts labor mobility, and weakens workers’ bargaining positions in industrial relations. Using a normative juridical research method, this study examines the relevant provisions of Labor Law, implementing regulations, principles of worker protection, and industrial relations theories to assess the legality and implications of diploma retention. The findings indicate that the retention of workers’ diplomas by companies contradicts the principles of freedom to work, non-discrimination, and the protection of personal documents. Legal protection for workers can be pursued through administrative, civil, and criminal mechanisms, as well as dispute resolution procedures under Law Number 2 of 2004 on Industrial Relations Dispute Settlement. This study concludes that diploma retention not only causes material and immaterial losses to workers but also negatively impacts the harmony of industrial relations. Therefore, consistent law enforcement and clearer regulations are necessary to prevent diploma retention practices and ensure the protection of workers’ rights